FINANCIAL DEEPENING AND INTEREST RATE RELATIONSHIP IN FACING THE ASEAN ECONOMIC COMMUNITY 2015: VECM AND PANEL DATA APPROACH - Lukman Hakim (Quantitative Economics Journal, 2016)
The relationship of the financial deepening to the interest rate has become an important study for the Southeast Asia countries, especially preparation forentering the ASEAN Economic Community (AEC) in 2015. This study will explore the effect of interest rates on deposits and credit to the financial deepening in ASEAN 5. By using VECM showed that Indonesia, the Philippines and Singapore possessed a similar pattern where lending rates negatively affect financial deepening, while the deposit rate positive effect. In contrast to Malaysia and Thailand, deposit rates had a negative impact on financial depth, while the loan interest rate was positive. Meanwhile, using panel data for the ASEAN 5 showed that the effect of interest rates on loans to the depth of the financial sector is negative, whereas the effect of deposit rate was positive